Determinan Pemanfaatan Pelayanan Kesehatan di Puskesmas Kasihan 1 Pada Era New Normal - Abdullah Hanif Mustofa; Fatma Siti Fatimah; Raden Jaka Sarwadhamana (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Community Health Center (Puskesmas) is the spearhead of health services in Indonesia that aims to provide health services evenly, integratedly, affordably and thoroughly. The use of health services during the COVID-19 pandemic makes people afraid to seek treatment so that there is a decrease in visits to health centers for treatment so that the utilization of health services becomes less optimal.to know the factors related to the utilization of health services in Puskesmas Kasihan 1 in the new normal era. This type of research is quantitative with cross sectional research design. The sample in this study was all outpatient units at Puskesmas Kasihan 1 Bantul Yogyakarta. Participants were recruited using accidental sampling techniques. The sample numbered 106 respondents. Data analysis used in this study is a multivariate analysis with logistic regression statistical tests.it was obtained that faktors related to the utilization of health services in the new normal era are age, gender, health insurance and disease history factors. The most related factor is the history of disease. A person who has a history of disease will routinely check themselves into the puskesmas kasihan 1 during the COVID-19 pandemic or during the adaptation of new habits (New Normal) while complying with health protocols. with a value of p = 0,000 (p<0,05) with an OR value of 55,692.